Is she really going out with him? ebook - Cousens, Sophie (2024)
AN INSTANT USA TODAY BESTSELLER  A LibraryReads Pick A hilarious love story about a disillusioned divorcée who agrees to let her children play matchmaker . Columnist Anna Appleby has left her love life behind after a painful divorce. Who needs a man when she has two kids, a cat, and uncontested control of the TV remote? Besides, she’d rather be single than subject herself to the hell of online dating. But her office rival is vying for her column, and no column means no stable source of income. In a desperate attempt to keep her job, Anna finds herself pitching a unique angle: seven dates, all found offline, chosen by her children. From awkward encounters to unexpected connections, Anna gamely begins to put herself out there, asking out waiters, the mailman, and even her celebrity crush. But when a romantic connection appears where she least expected it, will she be brave enough to take another chance on love?